Gonadal health benefits of black cumin (Nigella sativa) seed oil on chronic lead-exposed male Wistar rats - Afrina Mustari; Mahabub Alam; Samia Rashid; A.G.M.Sofi Uddin Mahamud; Mohammad Alam Miah; Emdadul Hauqe Chowdhury (Journal of Advanced Biotechnology and Experimental Therapeutics)
Lead (Pb) is a highly toxic heavy metal that can cause harm even at extremely low concentrations and damage various organs, including those of reproduction. Medical herbs like Nigella sativa include antioxidants that have been shown to enhance spermatogenesis and male fertility. This research aimed to investigate the gonadal health benefits of Nigella sativa seed oil (NSO) as an antidote in male rats exposed to chronic Pb toxicity. Forty rats were divided into four groups: a control group, a group exposed to Pb acetate (75 mg/kg body weight), a group given NSO (1ml/kg feed), and a group exposed to Pb acetate (75 mg/kg body weight) along with NSO (1ml/kg feed). Pb was administered through water, while NSO with fed for 16 weeks. Rats were euthanized, blood was obtained, and serum was prepared to perform hormonal study. Sperm concentration and motility along with testis weight and diameter were measured. The testes were collected for histology. The findings indicated a significant drop in serum concentrations of testosterone and thyroxin (T4) in Pb-exposed rats, whereas NSO demonstrated a remarkable ability to restore these hormone levels. Moreover, Pb exposure led to a notable reduction in sperm motility, sperm concentration, testis weight, and testis diameter, accompanied by seminiferous tubule degeneration. However, the administration of NSO effectively counteracted the adverse effects induced by chronic Pb exposure in rats. Together, these findings revealed the gonadoprotective effects of NSO against lead toxicity, suggesting its preventive as well as therapeutic potential in preserving the testicular function of rats exposed to chronic Pb toxicity. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 44-54]